Penerapan Aplikasi Quizizz sebagai Metode Evaluasi dalam Pembelajaran Digital Marketing - Aulia Fitriyani (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
Interest is one of the things that can affect a person's learning. A person interested in a subject will naturally feel happy to participate in the study. When a person feels happy, it will be easier to understand the material being taught so that learning outcomes will be maximum. The evaluation of learning determines student learning outcomes. As a facilitator, the teacher must be able to make learning fun. The Quizizz application is a web tool that can be used as an exciting and fun learning evaluation medium. This study aims to know students' perceptions of the application of Quizizz as an evaluation method in creating a pleasant learning atmosphere to increase students' interest in learning, especially in Digital Marketing subjects.